Sulfonated ZrO2-TiO2 nanorods as efficient solid acid catalysts for heterogeneous esterification of palmitic acid - Fan, Mingming; Si, Zhikun; Sun, Wenjuan; Zhang, Pingbo (Fuel (Guildford), 2019)
[Display omitted] •ZrO2-TiO2 nanorods with stable chemical property and large specific surface area.•ZrO2-TiO2-SO3H and ZrO2-TiO2@SO42− nanorods exhibit Brønsted and Lewis acid sites.•Esterification of palmitic acid is mainly catalyzed by Brønsted acid sites.•ZrO2-TiO2-SO3H nanorods show strong catalytic activity and excellent reusability.•Optima reaction condition was studied by the means of single factors. Two types of efficient and novel sulfonated ZrO2-TiO2 nanorods solid acid catalysts, designed as ZrO2-TiO2-SO3H nanorods and ZrO2-TiO2@SO42− nanorods, were prepared for the production of biodiesel by esterification of palmitic acid. The ZrO2-TiO2 nanorods were used as carrier and sulfonated by two different methods: post-gifting method and impregnation method. These catalysts were characterized by FT-IR, Pyridine-FT-IR SEM, TEM, EDS, BET, TGA and XRD to study their properties. The results indicated that the morphologies of ZrO2-TiO2 nanocomposites were unique nanorods. The two catalysts had high content of sulfate groups, which were demonstrated by the weight ratio of S/(Zr + Ti) and obvious peaks of Brønsted acid sites. As the results, ZrO2-TiO2-SO3H and ZrO2-TiO2@SO42− revealed strong catalytic activities in the esterification of palmitic acid. Although ZrO2-TiO2@SO42− nanorods (acidity = 3.4 mmol/g) appealed stronger catalytic activity than ZrO2-TiO2-SO3H nanorods (acidity = 1.9 mmol/g) due to its higher acidities, ZrO2-TiO2-SO3H nanorods exhibited higher reusability, and the yield of biodiesel was more than 85% after 5 successive uses, which indicated that the method of sulfonation can deeply affect properties of catalysts.